Highly-ordered layered double-ceramic fiber aerogel and preparation method thereof

The highly ordered layered double-ceramic fiber aerogel was prepared by impregnation growth method, which solved the problems of insufficient rigidity and thermal conductivity of traditional ceramic aerogels, achieved high flexibility and low thermal conductivity, and was suitable for the field of thermal insulation.

CN119707520APending Publication Date: 2025-03-28YANGTZE DELTA REGION INST (QUZHOU) UNIV OF ELECTRONIC SCI & TECH OF CHINA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411918827.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Due to the rigidity and brittleness of the internal partial network structure, traditional ceramic aerogels are difficult to promote and apply on a large scale in industry and life, and their thermal conductivity and thermal stability are insufficient.

Method used

A highly ordered layered double-ceramic fiber aerogel was prepared by impregnation growth method, and a layered structure was formed by vacuum suction filtration, and a three-dimensional network structure was formed by capillary water absorption effect, which enhanced the connection and compressive resistance of the fiber skeleton.

Benefits of technology

The high flexibility and low thermal conductivity of the aerogel are achieved, which significantly improves its mechanical properties and thermal insulation properties, and reduces the complexity and cycle of the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707520A_ABST
    Figure CN119707520A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of functional nano porous materials, and particularly discloses highly-ordered layered double ceramic fiber aerogel and a preparation method thereof. The invention aims to consider the structural stability and application efficiency of the material, so that the material has unique advantages in the field of heat preservation and heat insulation. According to the main scheme, the preparation method comprises the following steps: dissolving metal alkoxide and a thickening agent to prepare a spinning solution, preparing two ceramic nanofibers through electrostatic spinning, and carrying out vacuum filtration on the ceramic nanofibers subjected to heat treatment to form a fiber membrane, then immersing the fiber membrane into an aqueous solution, promoting self-assembly of fibers to form a porous structure by utilizing a capillary water absorption effect of tiny holes in a fiber skeleton, and finally performing freeze drying and high-temperature calcination to obtain the highly-ordered layered double-ceramic fiber aerogel. The aerogel is composed of a highly ordered layered fiber skeleton, and has excellent mechanical properties and ultralow heat conductivity coefficient. The method is widely applied to the heat-insulating field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional nanoporous materials and provides a highly ordered layered double ceramic fiber aerogel and a preparation method thereof. Background Art

[0002] Aerogel is a special type of porous material that has low density, high porosity, large specific surface area and excellent thermal stability. It is widely used in various fields such as thermal insulation, sound insulation, catalyst carriers, energy storage materials, filter materials, sensors, etc. Especially in the field of thermal insulation, ceramic aerogel relies on the advantages of its own 3D network interconnection structure combined with the heat resistance of the ceramic material itself, and usually exhibits extremely low thermal conductivity and extremely high thermal stability. However, traditional ceramic aerogels synthesized by the sol-gel method have a "pearl chain" fractal network structure composed of nanoparticles. The neck area between particles lacks freedom of movement and is difficult to deform. It exhibits rigidity and brittleness, making it difficult to promote and apply traditional ceramic aerogels on a large scale in industry and life.

[0003] To address the problem of high thermal conductivity and insufficient thermal stability of aerogels, researchers combined nanofibers with nanoparticles, which greatly improved the thermal stability of aerogels and reduced the thermal conductivity of aerogels, but the material still lacked flexibility or elasticity (Chemical Engineering Journal, 2021, 411: 128402). With the advancement of electrospinning technology, it has become a reality to be able to prepare fibers with high aspect ratios in the laboratory. Donghua University used a drum-type electrospinning collector to produce ceramic fiber membrane aerogels. The high degree of cross-linking produced by this method not only improved the flexibility of ceramic aerogels, but also added more interfaces to effectively suppress thermal radiation. However, this preparation method requires the materials to be stacked layer by layer, which significantly increases the overall workload of preparing aerogels (ACS Nano 2020, 14, 15616-15625).

[0004] Although previous studies have solved the two major problems of brittleness and high thermal conductivity of traditional aerogels, the complexity of the preparation process has greatly increased. The present invention adopts an impregnation growth method to prepare highly ordered layered dual ceramic fiber aerogels, which effectively shortens the preparation cycle of aerogels and reduces the process difficulty. In this method, the fibers naturally form a layered structure through vacuum filtration, and then undergo a simple impregnation step to form a three-dimensional network structure. The resulting fiber aerogel not only maintains extremely high flexibility, but also has very low thermal conductivity. Summary of the invention

[0005] In order to meet the current challenges, it was found during the experiment that nanofibers can naturally form a layered stacking structure during vacuum filtration. In addition, the two nanofibers produce special overlaps during the filtration process. The alumina nanofibers with a smaller diameter will naturally wrap around the surface of the silica nanofibers due to their higher surface free energy, thereby enhancing the connection of the silica nanofiber skeleton. Furthermore, by utilizing the capillary water absorption effect of the tiny pores in the fiber skeleton, these pores can absorb water and form a layered three-dimensional network structure. This discovery not only improves the mechanical properties of the fiber aerogel, but also significantly improves its thermal insulation performance. Therefore, this three-dimensional nanofiber aerogel has a good application prospect and is particularly suitable for use in the field of thermal insulation. One of the main purposes of the invention is to provide a method for preparing a highly ordered layered dual ceramic fiber aerogel using an impregnation growth method, which aims to take into account the structural stability and application efficiency of the material, so that it can show its unique advantages in the field of thermal insulation.

[0006] The invention provides a highly ordered layered double ceramic fiber aerogel, comprising a layered three-dimensional network structure composed of silicon dioxide nanofibers and aluminum oxide nanofibers.

[0007] The present invention also provides a method for preparing a highly ordered layered double ceramic fiber aerogel, comprising the following steps:

[0008] Step 1, obtaining silicon dioxide nanofibers and aluminum oxide nanofibers by electrospinning, and subjecting the fibers to high temperature treatment, wherein the high temperature treatment temperature is 800° C., the heating rate is 5° C. / min, and the holding time is 2 hours;

[0009] Step 2, mixing the silicon dioxide nanofibers and the aluminum oxide nanofibers in a weight ratio of 3:2 in water and performing vacuum filtration to obtain a mixed fiber membrane;

[0010] Step 3: immerse the mixed fiber membrane in a silica sol solution, utilize the capillary water absorption phenomenon to promote the fiber self-assembly to form a highly ordered layered ceramic fiber aerogel precursor, and obtain a dual ceramic fiber aerogel through freeze drying and high-temperature calcination.

[0011] In the above scheme, the silicon oxide nanofibers and aluminum oxide nanofibers described in step 1 are obtained as follows:

[0012] Step 1-1, mixing aluminum isopropoxide, aluminum chloride hexahydrate, zirconium acetate and deionized water, adding an acidic solution to accelerate the hydrolysis reaction, adding ethanol as a stabilizer, and stirring at room temperature to form an aluminum oxide electrospinning precursor solution;

[0013] Step 1-2, adding polyethylene oxide to the precursor solution of step 1-1, stirring at room temperature, so that the viscosity of the precursor solution reaches 0.1 to 10 Pa·s, preferably 0.5 to 5 Pa·s, to obtain an aluminum oxide electrospinning solution;

[0014] Step 1-3, tetraethyl orthosilicate is mixed with deionized water, an acidic solution is added to accelerate the hydrolysis reaction, and the mixture is stirred at room temperature to form a silicon dioxide electrospinning precursor solution;

[0015] Step 1-4: Add polyethylene oxide to the precursor solution of step 1-3, and stir at room temperature to make the viscosity of the precursor solution reach 0.1 to 10 Pa·s, preferably 0.5 to 5 Pa·s, to obtain a silicon oxide electrospinning solution.

[0016] In the above scheme, in step 1-1, the acidic solution is acetic acid, which is used to accelerate the hydrolysis reaction and perform the chelation reaction. The concentration of acetic acid is 0.002-0.01 mol / L, the room temperature is 15-35°C, and the weight ratio of water, ethanol and acetic acid is 1:1:0.375;

[0017] In step 1-2, the weight concentration of the polyethylene oxide is 0.5 to 3 wt%;

[0018] In step 1-3, the acidic solution is phosphoric acid, which is used to accelerate the hydrolysis reaction and perform the chelating reaction. The concentration of phosphoric acid is 0.002-0.01 mol / L, the room temperature is 15-35° C., and the weight ratio of tetraethyl orthosilicate, deionized water and phosphoric acid is 1:1:0.01;

[0019] In step 1-4, the weight concentration of the polyethylene oxide is 0.5 to 3 wt %;

[0020] In the above scheme, the electrospinning voltage is 10 to 30 kV, preferably 15 to 25 kV;

[0021] The vertical distance between the electrospinning nozzle and the receiver is 10 to 30 cm, preferably 15 to 25 cm;

[0022] and / or

[0023] The electrospinning environment temperature is: 20-30°C, preferably 25-29°C;

[0024] The humidity of the electrospinning environment is 45-75% rh, preferably 55-65% rh.

[0025] In the above scheme, the weight ratio of nanofibers to water is 0.003:1.

[0026] In the above scheme, in step 3, the freeze-drying treatment sequentially includes: liquid nitrogen freezing for 1 to 20 minutes and room temperature freeze-drying treatment for 10 to 72 hours, wherein the room temperature is 15 to 35°C;

[0027] In the above scheme, in step 3, the high temperature calcination is carried out as follows:

[0028] The temperature is raised to 200-500°C at a heating rate of 0.5-5°C / min, maintained for 0.5-2h, and then raised to 700-1000°C at a heating rate of 0.5-5min, and maintained for 0.5-5h.

[0029] In the above scheme, in step 3, the high temperature calcination is carried out as follows:

[0030] The temperature was raised to 300-400°C at a heating rate of 0.5-2°C / min, maintained for 0.5-1.5h, and then raised to 750-900°C at a heating rate of 0.5-2°C / min, maintained for 1-3h.

[0031] Because the present invention adopts the above technical means, it has the following beneficial effects:

[0032] (1) The preparation method adopted by the present invention is simpler than the existing method for obtaining layered ceramic fiber aerogel.

[0033] (2) The present invention ingeniously utilizes the tiny cavities composed of nanofibers to produce a capillary water absorption effect, thereby promoting the self-assembly of the fiber skeleton.

[0034] (3) The present invention utilizes two different fibers to form a wrapped overlapping structure under the drive of vacuum filtration, thereby giving the fiber skeleton better compression resistance and elasticity.

[0035] (4) The highly ordered layered ceramic nanofiber aerogel obtained by the method of the present invention can be used in the field of thermal insulation. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The present invention proposes a preparation flow chart of a highly ordered layered double ceramic fiber aerogel using an impregnation growth method

[0037] Figure 2 is a cross-sectional microstructure diagram of the ceramic fiber aerogel of Example 1;

[0038] Figure 3 is the mechanical properties diagram of the aerogel prepared in Example 1, Figure 3 In the left graph, ε represents strain, which is the ratio of the deformation of an object under the action of external force to its original size. The left graph shows the stress-strain relationship curves of materials with three different ε() values ​​(20%, 40%, 60%) during compression. Specifically:

[0039] The black line, red line and blue line represent the stress-strain curves of aerogel under three different strains.

[0040] The curve shows that as the strain increases, the compressive stress also gradually increases. The aerogel can maintain good elasticity under compression of ε=20%, 40%, and 60%, indicating that the dual ceramic fiber aerogel in this study can withstand compressive strain within ε=60%.

[0041] Figure 3 The right graph in the middle shows the stress-strain relationship of the same material under different cycle numbers. Four cycles (cycle 1, cycle 10, cycle 50, cycle 100) are listed in the figure, and the data of each cycle is represented by a line of a different color:

[0042] The black line corresponds to cycle 1, which shows the response during the first loading.

[0043] The red line corresponds to cycle 10 and reflects the behavior of the material at the 10th cycle.

[0044] The blue line corresponds to cycle 50, reflecting the impact of the 50th cycle.

[0045] The green line corresponds to cycle 100, which represents the properties of the material after 100 cycles.

[0046] From the graph on the right, we can see that with the increase in the number of cycles, the compressive stress of the material under the same strain does not decrease significantly, which suggests that the material exhibits good fatigue resistance during repeated loading.

[0047] Figure 4 is a graph of the thermomechanical stability of the aerogel prepared in Example 1;

[0048] The two pictures above (a, b)

[0049] Figure 4 (a) Storage modulus-frequency:

[0050] The figure shows how the storage modulus of the material changes with frequency at four different temperatures (-100℃, 0℃, 200℃, 400℃).

[0051] Different symbols represent different temperatures: diamond (-100℃), triangle (200℃), circle (0℃),

[0052] Square (400℃).

[0053] It can be seen that at all temperatures, the storage modulus does not change much with frequency and remains at about 105 about.

[0054] Figure 4 (b) Loss modulus-frequency:

[0055] This section shows the variation of the loss modulus of the material with frequency at different temperatures.

[0056] Different symbols represent different temperatures: diamond (-100℃), triangle (200℃), circle (0℃),

[0057] Square (400℃).

[0058] The loss modulus also varies little with frequency, with a value range of about 10 3 Pa to 10 4 Between Pa.

[0059] The two pictures below (c, d)

[0060] Figure 4 (c) Damping ratio-frequency:

[0061] This section shows how the damping ratio of a material varies with frequency at different temperatures.

[0062] Symbols also represent different temperatures: diamond (-100°C), triangle (200°C), circle (0°C),

[0063] Square (400℃).

[0064] The damping ratio remains stable over the entire frequency range and is approximately 10 -2 .

[0065] Figure 4 Medium (d) modulus-temperature:

[0066] This section shows the variation of storage modulus and loss modulus with temperature.

[0067] The black solid line represents the storage modulus, the blue dashed line represents the loss modulus, and the red dashed line represents the damping ratio.

[0068] As can be seen from the figure, there is no obvious fluctuation in the three lines, indicating that the material has good mechanical stability.

[0069] Figure 5 The figure below is a thermal insulation demonstration of the aerogel prepared in Example 1. The figure shows the temperature distribution of the aerogel at different times. The figure shows an 8 mm diameter product placed on a butane blowtorch. The right side is a color heat map of the temperature change of the object over time.

[0070] The figure shows how the outer temperature of the material changes with time at six time points (30 seconds, 1 minute, 2 minutes, 6 minutes, 10 minutes, and 12 minutes) during the heating process.

[0071] It can be seen that at 30 seconds, the central area of ​​the object begins to heat up and the temperature reaches 36.0°C.

[0072] At 1 minute, the temperature gradually increased to 43.7°C.

[0073] After 2 minutes, the temperature gradually increased to 65.3°C.

[0074] At 6 minutes, the temperature reached 85.5℃.

[0075] At 10 minutes, the temperature was maintained at 88.9°C.

[0076] At 12 minutes, the temperature reached 87.6°C.

[0077] From the figure, we can see that the surface temperature of the spray gun reached 780℃ after 10 minutes, and the outer surface temperature of the material remained basically stable at 87℃, proving that the material has excellent thermal insulation ability in high temperature environment; Figure 6 This is a cross-sectional microstructure diagram of the ceramic fiber aerogel of Example 2. DETAILED DESCRIPTION

[0078] The following is a detailed description of the embodiments of the present invention. Although the present invention will be described and illustrated in conjunction with some specific embodiments, it should be noted that the present invention is not limited to these embodiments. On the contrary, modifications or equivalent substitutions made to the present invention should all be included in the scope of the claims of the present invention.

[0079] In addition, in order to better illustrate the present invention, numerous specific details are given in the following specific embodiments. It will be understood by those skilled in the art that the present invention can also be implemented without these specific details.

[0080] The raw materials used in the examples and comparative examples can be purchased or prepared by methods disclosed in the prior art.

[0081] There is no particular limitation on how to obtain the electrospun nanofibers described in step 1. The nanofibers can be purchased directly or prepared by the methods disclosed in the prior art. The steps are preferably, but not limited to, the following steps. In a preferred embodiment, the electrospun nanofibers described in step 1 are obtained as follows:

[0082] Step 1-1, aluminum isopropoxide, aluminum chloride hexahydrate, zirconium acetate and deionized water are mixed, an acidic solution is added to accelerate the hydrolysis reaction, ethanol is added as a stabilizer, and the mixture is stirred at room temperature;

[0083] Step 1-2: Add polyethylene oxide to the step 1-1, stir at room temperature, and make the viscosity of the precursor solution reach 0.1 to 10 Pa·s, preferably 0.5 to 5 Pa·s, to obtain the electrospinning solution.

[0084] Step 1-3, tetraethyl orthosilicate is mixed with deionized water, an acidic solution is added to accelerate the hydrolysis reaction, and the mixture is stirred at room temperature;

[0085] Step 1-4: Add polyethylene oxide to step 1-3, stir at room temperature, and make the viscosity of the precursor solution reach 0.1 to 10 Pa·s, preferably 0.5 to 5 Pa·s, to obtain a silicon oxide electrospinning solution.

[0086] The role of the polyethylene oxide is to act as a dispersant to adjust the solution concentration and avoid the problem of difficult molding in the electrospinning stage.

[0087] If the electrospinning solution is prepared by itself, it is mainly obtained by weighing, fully dissolving and homogenizing.

[0088] In a preferred embodiment, in step 1-1, the weight ratio of aluminum chloride hexahydrate, aluminum isopropoxide, zirconium acetate and deionized water is: 1.26:2.66:0.55:12.6.

[0089] In a preferred embodiment, in step 1-1, the acidic solution is used to accelerate the hydrolysis reaction, and an acetic acid solution is used for the chelating reaction treatment.

[0090] In a preferred embodiment, in step 1-1, the weight ratio of water, ethanol and acetic acid is 1:1:0.375.

[0091] In a preferred embodiment, in step 1-2, the weight concentration of the polyethylene oxide is 0.5 to 3 wt %.

[0092] In a further preferred embodiment, in step 1-2, the weight concentration of polyethylene oxide is preferably 1 to 1.5 wt %.

[0093] In a preferred embodiment, in steps 1-3, the weight ratio of tetraethyl orthosilicate, deionized water and phosphoric acid is 1:1:0.01.

[0094] In a preferred embodiment, in step 1-4, the weight concentration of the polyethylene oxide is 0.5 to 3 wt %.

[0095] In a further preferred embodiment, in step 1-4, the weight concentration of polyethylene oxide is preferably 1 to 1.5 wt %.

[0096] Step 2: Mix the two fibers in water according to a specific ratio and obtain a mixed fiber membrane by vacuum filtration.

[0097] In a preferred embodiment, in step 2, the ratio of silicon oxide fiber to aluminum oxide fiber is 3:2.

[0098] In a preferred embodiment, in step 2, the weight ratio of nanofibers to water is 0.003:1.

[0099] In the present invention, silica fibers and alumina fibers are fully mixed in water using a homogenizer, and the mixed fiber solution is placed in a vacuum filter to filter the nanofibers onto filter paper. The nanofibers spontaneously form a layered structure under the drive of vacuum filtration, and the two nanofibers form a coated overlapping structure during the mixing process, further promoting the connection between the silica nanofibers serving as a framework structure.

[0100] In a preferred embodiment, in step 3, the fiber membrane is immersed in a silica sol solution, and the capillary water absorption phenomenon is used to promote the self-assembly of the fibers to form a highly layered ceramic fiber aerogel precursor, and the ceramic fiber aerogel is obtained through freeze drying and high-temperature calcination.

[0101] In a further preferred embodiment, step 3 comprises the following sub-steps:

[0102] Step 3.1, immersing the filtered fiber membrane in a 4 wt % tetraethyl orthosilicate aqueous solution to allow it to fully swell;

[0103] Step 3.2, freeze-drying the expanded aerogel precursor in step 3.1;

[0104] Step 3.3: calcining at high temperature to obtain the highly layered ceramic nanofiber aerogel.

[0105] In a preferred embodiment, the weight ratio of tetraethyl orthosilicate to water in the silica sol described in step 3.1 is 0.01:1.

[0106] In a preferred embodiment, in step 3.1, the fiber membrane is immersed in the silica sol for 1 min.

[0107] In a preferred embodiment, in step 3.2, the freeze-drying treatment sequentially includes: liquid nitrogen freezing for 1 to 20 minutes and room temperature freeze-drying treatment for 10 to 72 hours.

[0108] Wherein, the room temperature is 15-35°C, preferably 20-30°C.

[0109] In a preferred embodiment, in step 3.3, the high temperature calcination is carried out as follows: heating to 200-500°C at a heating rate of 0.5-5°C / min, maintaining for 0.5-2h, and then heating to 700-1000°C at a heating rate of 0.5-5min, maintaining for 0.5-5h.

[0110] In a further preferred embodiment, the heat curing treatment is carried out as follows: heating to 300-400°C at a heating rate of 0.5-2°C / min, maintaining for 0.5-1.5h, and then heating to 750-900°C at a heating rate of 0.5-2°C / min, maintaining for 1-3h.

[0111] like Figure 1 As shown, it is a preparation flow chart of the highly layered dual ceramic fiber aerogel prepared by the impregnation growth method in the invention

[0112] The present invention provides a method for preparing a highly ordered layered double ceramic fiber aerogel by using an impregnation growth method, comprising the following steps:

[0113] Step 1, preparing silicon oxide nanofibers and aluminum oxide nanofibers by electrospinning;

[0114] Step 2, fully mixing the nanofibers obtained in step 1 in water, and obtaining a fiber membrane by vacuum filtration;

[0115] Step 3: Immerse the fiber membrane obtained in step 2 in silica sol to expand it, and then obtain a highly ordered layered double ceramic fiber aerogel after freeze drying and high temperature treatment.

[0116] The specific steps include:

[0117] Step 1, adding zirconium acetate, aluminum isopropoxide, aluminum chloride hexahydrate, acetic acid, and anhydrous ethanol into deionized water, and stirring at room temperature for 10 hours to obtain an aluminum oxide electrospinning precursor sol;

[0118] Tetraethyl orthosilicate, phosphoric acid and water were stirred at room temperature for 10 h to obtain a silica electrospinning precursor sol;

[0119] Adding polyethylene oxide powder into deionized water, stirring at room temperature for 8 hours, to obtain polyethylene oxide aqueous solution; mixing polyethylene oxide and two precursor sols, stirring at room temperature for 2 hours to obtain a spinning solution;

[0120] Step 2, fully mixing the two nanofibers in water, and then obtaining a fiber membrane by vacuum filtration;

[0121] Step 3: Immerse the fiber membrane obtained in step 2 in a silica sol solution, use the capillary water absorption phenomenon to promote the fiber self-assembly to form a highly ordered layered ceramic fiber aerogel precursor, and obtain a dual ceramic fiber aerogel through freeze drying and high-temperature calcination.

[0122] Example 1

[0123] This embodiment provides a method for preparing a highly ordered layered double ceramic fiber aerogel by an impregnation growth method, comprising the following steps:

[0124] The first step: preparing an alumina electrospinning solution and a silica electrospinning solution, weighing 1.26 g of aluminum chloride hexahydrate and 2.665 g of aluminum isopropoxide and dissolving them in a mixed solution of 30 g of water, ethanol and acetic acid at room temperature, wherein the weight ratio of water, ethanol and acetic acid is 1:1:0.375, stirring for 10 hours until the solution is transparent, adding 1.19 g of zirconium acetate and 0.35 g of polyethylene oxide to the mixed solution, and stirring at room temperature for 8 hours to form the alumina electrospinning precursor solution;

[0125] 9.3 g of deionized water, 10.7 g of tetraethyl orthosilicate and 0.01 g of phosphoric acid were weighed and mixed, and stirred at room temperature for 8 hours until transparent. 0.2 g of polyethylene oxide was added to the mixed solution, and stirred at room temperature for 8 hours to form the silica electrospinning precursor solution.

[0126] Step 2: Load the spinning solution into the syringe for electrospinning, wherein the injection speed is 0.3 mL / h, the spinning voltage is set to 20 kV, the vertical distance between the electrospinning nozzle and the collector is 20 cm, the electrospinning environment temperature is 28° C., and the electrospinning environment humidity is 60% rh.

[0127] Step 3: Mix the two nanofibers in water and use a homogenizer to evenly disperse the two fibers to obtain a uniform and stable fiber dispersion, wherein the speed of the homogenizer is 10,000 rpm and the dispersion time is 10 minutes.

[0128] Step 4: Place the fiber dispersion in a vacuum filter to filter the fibers into a mixed fiber membrane.

[0129] Step 5: Place the fiber membrane in the silica sol to expand, and then freeze-dry and high-temperature calcination to obtain a highly layered dual-ceramic nanofiber aerogel. The freezing temperature is -50°C, the drying temperature is 60°C, and the time is 72 hours; use a tubular furnace in an argon atmosphere, and heat it to 800°C at a rate of 2°C / min, and keep it warm for 30 minutes.

[0130] like Figure 2 The cross-sectional microstructure of the ceramic fiber aerogel in this embodiment is shown in FIG. Figure 2It can be seen that the aerogel has a highly layered structure; Figure 3 It can be seen that the aerogel has good elasticity and mechanical strength; Figure 4 It can be seen that the aerogel has good thermomechanical stability. Figure 5 It can be seen that the aerogel performs well in thermal insulation.

[0131] Example 2

[0132] This embodiment provides a method for preparing a highly ordered layered dual ceramic fiber aerogel by an impregnation growth method, comprising the following steps:

[0133] Step 1: Prepare an alumina electrospinning solution and a silica electrospinning solution, weigh 1.26 g of aluminum chloride hexahydrate and 2.665 g of aluminum isopropoxide, dissolve them in a mixed solution of 30 g of water, ethanol and acetic acid at room temperature, the weight ratio of water, ethanol and acetic acid is 1:1:0.375, stir for 10 hours until the solution is transparent, add 1.19 g of zirconium acetate and 0.35 g of polyethylene oxide to the mixed solution, and stir at room temperature for 8 hours to form the alumina electrospinning precursor solution;

[0134] 9.3 g of deionized water, 10.7 g of tetraethyl orthosilicate and 0.01 g of phosphoric acid were weighed and mixed, and stirred at room temperature for 8 hours until transparent. 0.2 g of polyethylene oxide was added to the mixed solution, and stirred at room temperature for 8 hours to form the silica electrospinning precursor solution.

[0135] Step 2: Load the spinning solution into the syringe for electrospinning, wherein the injection speed is 0.3 mL / h, the spinning voltage is set to 20 kV, the vertical distance between the electrospinning nozzle and the collector is 20 cm, the electrospinning environment temperature is 28° C., and the electrospinning environment humidity is 60% rh.

[0136] Step 3: Mix the two nanofibers in water and use a homogenizer to evenly disperse the two fibers to obtain a uniform and stable fiber dispersion, wherein the speed of the homogenizer is 10,000 rpm and the dispersion time is 20 minutes.

[0137] Step 4: Place the fiber dispersion in a vacuum filter to filter the fibers into fiber membranes.

[0138] Step 5: Place the fiber membrane in the silica sol to expand, and then freeze-dry and high-temperature calcination to obtain a highly layered dual-ceramic nanofiber aerogel. The freezing temperature is -50°C, the drying temperature is 60°C, and the time is 72 hours; use a tubular furnace in an argon atmosphere, and heat it to 800°C at a rate of 2°C / min, and keep it warm for 30 minutes.

[0139] like Figure 6As shown, after the dispersion time increased from 10 minutes to 20 minutes, the fibers were more fully mixed, the alumina nanofibers wrapped the silica nanofibers more obviously, and a more obvious layered skeleton appeared inside the aerogel.

Claims

1. A highly ordered layered double ceramic fiber aerogel, characterized in that: The invention comprises a layered three-dimensional network structure composed of silicon dioxide nanofibers and aluminum oxide nanofibers.

2. The method for preparing a highly ordered layered double ceramic fiber aerogel according to claim 1, characterized in that: The following steps are involved: Step 1, obtaining silicon dioxide nanofibers and aluminum oxide nanofibers by electrospinning, and subjecting the fibers to high temperature treatment; Step 2, mixing the silicon dioxide nanofibers and the aluminum oxide nanofibers in a weight ratio of 3:2 in water and performing vacuum filtration to obtain a mixed fiber membrane; Step 3: Immerse the mixed fiber membrane in a silica sol solution, use the capillary water absorption phenomenon to promote the fiber self-assembly to form a highly ordered layered ceramic fiber aerogel precursor, and obtain a dual ceramic fiber aerogel through freeze drying and high-temperature calcination.

3. According to the method for preparing a highly ordered layered dual ceramic fiber aerogel according to claim 1, the silicon oxide nanofibers and aluminum oxide nanofibers in step 1 are obtained as follows: Step 1-1, mixing aluminum isopropoxide, aluminum chloride hexahydrate, zirconium acetate and deionized water, adding an acidic solution to accelerate the hydrolysis reaction, adding ethanol as a stabilizer, and stirring at room temperature to form an aluminum oxide electrospinning precursor solution; Step 1-2, adding polyethylene oxide to the precursor solution of step 1-1, stirring at room temperature, so that the viscosity of the precursor solution reaches 0.1 to 10 Pa·s, preferably 0.5 to 5 Pa·s, to obtain an aluminum oxide electrospinning solution; Step 1-3, tetraethyl orthosilicate is mixed with deionized water, an acidic solution is added to accelerate the hydrolysis reaction, and the mixture is stirred at room temperature to form a silicon dioxide electrospinning precursor solution; Step 1-4: Add polyethylene oxide to the precursor solution of step 1-3, and stir at room temperature to make the viscosity of the precursor solution reach 0.1 to 10 Pa·s, preferably 0.5 to 5 Pa·s, to obtain a silicon oxide electrospinning solution.

4. The method for preparing a highly ordered layered double ceramic fiber aerogel according to claim 2, characterized in that: In step 1-1, the acidic solution is acetic acid, which is used to accelerate the hydrolysis reaction and perform the chelating reaction. The concentration of acetic acid is 0.002-0.01 mol / L, the room temperature is 15-35° C., and the weight ratio of water, ethanol and acetic acid is 1:1:0.375; In step 1-2, the weight concentration of the polyethylene oxide is 0.5 to 3 wt%; In step 1-3, the acidic solution is phosphoric acid, which is used to accelerate the hydrolysis reaction and perform the chelating reaction. The concentration of phosphoric acid is 0.002-0.01 mol / L, the room temperature is 15-35° C., and the weight ratio of tetraethyl orthosilicate, deionized water and phosphoric acid is 1:1:0.01; In step 1-4, the concentration of the polyethylene oxide is 0.5 to 3 wt%.

5. The method for preparing a highly ordered layered double ceramic fiber aerogel according to claim 4, characterized in that: The electrospinning voltage is 10 to 30 kV, preferably 15 to 25 kV; The vertical distance between the electrospinning nozzle and the receiver is 10 to 30 cm, preferably 15 to 25 cm; The electrospinning environment temperature is: 20-30°C, preferably 25-29°C; The humidity of the electrospinning environment is 45-75% rh, preferably 55-65% rh. In step 1-3, the weight ratio of water to phosphoric acid is 1:1:0.

01.

6. The method for preparing a highly ordered layered double ceramic fiber aerogel according to claim 4, characterized in that: The weight ratio of nanofibers to water is 0.003:

1.

7. The method for preparing a highly ordered layered double ceramic fiber aerogel according to claim 4, characterized in that: In step 3, the freeze-drying treatment includes: liquid nitrogen freezing for 1 to 20 minutes and room temperature freeze-drying treatment for 10 to 72 hours, and the room temperature is 15 to 35°C.

8. The method for preparing a highly ordered layered double ceramic fiber aerogel according to claim 7, characterized in that: In step 3, the high temperature calcination is carried out as follows: the temperature is increased to 200-500° C. at a heating rate of 0.5-5° C. / min, maintained for 0.5-2 h, and then increased to 700-1000° C. at a heating rate of 0.5-5 min, and maintained for 0.5-5 h.

9. The method for preparing a highly ordered layered double ceramic fiber aerogel according to claim 7, characterized in that: In step 3, the high temperature calcination is carried out as follows: the temperature is increased to 300-400°C at a heating rate of 0.5-2°C / min, maintained for 0.5-1.5h, and then increased to 750-900°C at a heating rate of 0.5-2°C / min, maintained for 1-3h.

10. The preparation method according to claim 1, characterized in that: In step 1, the temperature of the high temperature treatment is 800° C., the heating rate is 5° C. / min, and the holding time is 2 hours.

Citation Information

Cited By

  • Semi-ordered high-curvature ceramic fiber aerogel, preparation method and continuous preparation system thereof

    CN121758193A